UMPSA Residents Hoist the National Flag to Enliven National Day 2023 - Nor Salwana, Mohammad Idris (UMPSA, 2023)
PAYA BESAR, August 11, 2023 - Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) held a National Flag Presentation Ceremony to further enhance the spirit of love for the country among UMPSA residents in conjunction with National Day 2023 with the theme 'Malaysia MADANI: Determination for Unity Fulfills Hope' (‘Malaysia MADANI: Tekad Perpaduan Penuhi Harapan’) for this year.